2013
DOI: 10.1155/2013/317456
|View full text |Cite
|
Sign up to set email alerts
|

Gsk-3βInhibitors Mimic the Cardioprotection Mediated by Ischemic Pre- and Postconditioning in Hypertensive Rats

Abstract: The aim of this study was to examine the effects of GSK-3β inhibitors compared with PRE and POS in spontaneously hypertensive rats (SHR). Isolated hearts were submitted to the following protocols: IC: 45 min global ischemia (GI) and 1-hour reperfusion (R); PRE: a cycle of 5 min GI and 10 minutes of R prior to 45 min GI; POS: three cycles of 30 sec GI/30 sec R at the start of R. Other hearts received lithium chloride (LiCl) or indirubin-3′-monoxime,5-iodo-(IMI) as GSK-3β inhibitors. All interventions reduced th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 46 publications
0
16
0
1
Order By: Relevance
“…GSK-3β-induced mPTP opening has been linked to increased vulnerability to infarction in hypertensive hypertrophied hearts [62], and its inhibition improves post-ischemic recovery in pressure-overload hypertrophied hearts [63]. Similarly, treatment with GSK-3 β inhibitors attenuated mitochondrial permeability and improved antioxidant activity in hearts from salt hypertensive rats [64]. However, additional studies are needed to confirm these findings and validate GSK-3β as a target therapy in hypertension.…”
Section: Mechanisms Of Mitoprotectionmentioning
confidence: 99%
“…GSK-3β-induced mPTP opening has been linked to increased vulnerability to infarction in hypertensive hypertrophied hearts [62], and its inhibition improves post-ischemic recovery in pressure-overload hypertrophied hearts [63]. Similarly, treatment with GSK-3 β inhibitors attenuated mitochondrial permeability and improved antioxidant activity in hearts from salt hypertensive rats [64]. However, additional studies are needed to confirm these findings and validate GSK-3β as a target therapy in hypertension.…”
Section: Mechanisms Of Mitoprotectionmentioning
confidence: 99%
“…Furthermore, the research team designed another study that intralipid was deprived of cardioprotection due to no capacity for upregulating the phosphorylation of Akt, ERK1/2, and their downstream target of GSK3β in the hypertrophic myocardium, but GSK3β inhibitor SB216763 failed to restore the intralipid cardioprotection (7), and it coincided with another study performed by Oei et al (65). On the contrary, some studies showed that GSK3β inhibitors imitated the cardioprotection afforded by ischemic conditioning and suggested that a decrease in mPTP by GSK3β/VDAC interaction was a crucial event (66). In addition, IpostC exerted cardioprotection in compensated hypertrophic myocardium induced by angiotensin II.…”
Section: Hypertension and Myocardial Hypertrophymentioning
confidence: 75%
“…The role for indirubin in cancer has been extensively reviewed [ 302 ]. With regard to the heart, indirubin and its derivatives protect against hyperglycemia-induced cardiac injury, aortic constriction-induced hypertrophy, I/R injury, hyperlipidemia-induced cardiac injury and diabetes-induced cardiomyopathy [ 97 , 98 , 99 , 100 , 303 , 304 ]. Cardiac protection was shown to be mediated in part through the attenuation of c-Jun-N-terminal kinase (JNK) signaling, caspase-3-directed apoptosis, and NF-ĸB expression [ 303 ].…”
Section: Phytochemicalsmentioning
confidence: 99%
“…Cardiac protection was shown to be mediated in part through the attenuation of c-Jun-N-terminal kinase (JNK) signaling, caspase-3-directed apoptosis, and NF-ĸB expression [ 303 ]. Others have reported that indirubin regulated GSK-3β signaling in order to protect cardiac function [ 97 , 98 , 99 , 100 , 304 ]. These results are interesting since class I HDACs have been shown to regulate GSK-3β signaling [ 150 ], JNK phosphorylation [ 50 ] and NF-κB activation [ 131 ].…”
Section: Phytochemicalsmentioning
confidence: 99%